The role of self-efficacy: Entrepreneurial knowledge and attitude toward entrepreneurship to entrepreneurial intention - Wibowo, Indi Deli Fiallo; Khan, Nadia Shadab (Universitas Ahmad Dahlan, 2024)
Purpose-Internal and-external factors certainly influence an individual's intention to start a business. Entrepreneurial intention needs to be fostered early so that the younger generation not only depends on existing jobs but also creates jobs and develops business ideas. Self-efficacy acts as a mediating variable in the influence of entrepreneurial knowledge and attitudes towards entrepreneurship on entrepreneurial intentions. Design/Methodology/Approach-The population of this study focused on the younger generation, especially students in Indonesia. The research data were obtained through an online questionnaire, and 95 respondents were obtained. The research data were analyzed using the Smart PLS software (version 4.0). Findings-Entrepreneurial knowledge proved to have no effect on entrepreneurial intention but proved to have a positive effect on self-efficacy. Self-efficacy has a positive effect on entrepreneurial intention. Self-efficacy did not mediate the effect of entrepreneurial knowledge on entrepreneurial intention. Attitude towards entrepreneurship has a positive effect on entrepreneurial intention and self-efficacy. Self-efficacy has been proven to mediate the effect of attitudes towards entrepreneurship on entrepreneurial intention. Research limitations/implications-For individuals, especially the younger generation, it is necessary to increase knowledge about entrepreneurship and develop an attitude towards entrepreneurship to encourage entrepreneurial intentions early on. In addition, to support entrepreneurial intentions, individuals must pay attention to other factors such as self-efficacy. Originality/value-This study analyzed the entrepreneurial intention of university students in Indonesia by considering the factors of entrepreneurial knowledge, attitude towards entrepreneurship, and self-efficacy.